Fabrication of pure porous CuO from microwave-synthesized MOF-199 by calcination in ambient air - Khac, Nam Ho Phung (International Journal of Advanced Engineering Research and Science, 2024)
Metal-organic frameworks with porous characteristics are applied in many fields. This study used it as a superior raw material source for making transition metal oxides. By calcining the copper 1,3,5-benzene tricarboxylate framework in ambient air, copper(II) oxide was produced. The calcination temperature was investigated in the range of 250 to 700 °C. At a calcination temperature of 550 °C, the resultant CuO has a homogeneous size and shape within the 1-2 um range. CuO’s surface area of 33.16 m2/g is more excellent than several other materials and technologies used in CuO manufacture. Utilizing CuO generated by the MOF-199 calcination process for enhanced oxidation catalysis in treating organic gases and vapors is based on the research findings.